Assessment of a Theoretical Model for Predicting Forced Convective Critical Heat Flux in Rod Bundles - Liu, Yang; Yin, Qian; Shan, Jianqiang; Zhang, Bo; Liu, Wei; Leung, L. K. H. (Frontiers in Energy Research, 2019)
This study proposes a theoretical model for predicting forced convective critical heat flux (CHF) in rod bundles based on the bubble crowding phenomenon. The theoretical model applied to the rod bundle is based on Weisman-Pei's basic tube model. In order to make it suitable for rod bundles in Pressurized Water Reactors (PWR), the flow and heat transfer characteristics of rod bundles are considered, including velocity distribution, flow patterns, the grid effect on CHF, and turbulence intensity. The theoretical model is applied together with the subchannel code ATHAS to assess it against uniformly heated CHF data obtained from a 5 × 5 rod bundle, and good agreement is observed.